Maladaptive schemas and aggressive behaviors in Peruvian adolescents - Castellanos Sánchez, Sara Marcelina Fátima (2022)
The aim of this research was to explore the link between early maladaptive schemas and aggressiveness in adolescents from Lima. We worked with 350 adolescents aged between 16 and 18 years. Jeffrey Young's Young's Schema Questionnaire - Short Form (YSQ-SF) was used and Buss and Perry's Aggressiveness Questionnaire (AQ) was applied for the second variable. Early maladaptive schemas were found to be related to aggression, except for self-sacrifice and emotional inhibition. The most predominant schema in males is distrust/abuse; in females self-sacrifice predominates.